Correlation of Body Mass Index and The Ability to Perform High Quality Cardiopulmonary Resuscitation: Manikin Study - Riki Ristanto (Babali Publisher, 2023)
Abstract. When assisting unconscious victims, the ability to perform High Quality Cardiopulmonary Resuscitation (HQ-CPR) is critical for optimizing rescue efforts. However, many factors contribute to achieving HQ-CPR, including the helper's BMI (body mass index). The aim of this study was to investigate the relationship between BMI and HQ-CPR proficiency. This study uses a correlational methodology. 101 nursing students from the Institut Teknologi, Sains, Dan Kesehatan (ITSK) RS Dr. Soepraoen who took part in Basic Trauma Cardiac Life Support (BTCLS) training in 2021 made up the population of this study. Purposive sampling was the sampling technique utilized, and 91 people were included in the sample. The BMI score of each CPR assistant serves as the independent variable in this study. The capacity for HQ-CPR is the dependent variable. On September 25 and 26, 2021, this study was conducted at ITSK RS Dr. Soepraoen. Given that the Kolmogorov-Smirnov correlation test analysis yielded a p-value of 0.000, it is possible to draw the conclusion that a person's BMI and their capacity to conduct HQ-CPR are related. The study's findings support the notion that a person's BMI has an impact on their capacity to execute HQ-CPR. A respondent who has a BMI in the mild to severe obesity range or a respondent with a BMI of extreme thinness is less likely to be able to conduct HQ-CPR than a respondent with a normal or mildly obese BMI. HQ-CPR is often maintained for the first two minutes of CPR by CPR providers with normal BMI. The fitness and weariness of a person are influenced by their BMI. A person with a healthy BMI usually has superior endurance because their heart and breathing processes, among other organ functions, are stronger.